The Compact with the Charter and Laws of the Colony of New Plymouth 102 (William Brigham ed., 1836) (enacted 1675) (Year-Round) - (:unkn) unknown (My University, 1675)
Required every one to bring arms to Sunday church services, furnishing six chargers of powder and shott. Penalty of two shillings for violations.
Keywords: REQUIRED POSSESSION